2015
DOI: 10.1007/s10533-015-0157-5
|View full text |Cite
|
Sign up to set email alerts
|

Chronic nitrogen fertilization and carbon sequestration in grassland soils: evidence of a microbial enzyme link

Abstract: Chronic nitrogen (N) fertilization can greatly affect soil carbon (C) sequestration by altering biochemical interactions between plant detritus and soil microbes. In lignin-rich forest soils, chronic N additions tend to increase soil C content partly by decreasing the activity of lignin-degrading enzymes. In cellulose-rich grassland soils it is not clear whether cellulose-degrading enzymes are also inhibited by N additions and what consequences this might have on changes in soil C content. Here we address whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 79 publications
(33 citation statements)
references
References 55 publications
2
28
0
3
Order By: Relevance
“…Our results are also similar to those from a 19‐yr grassland fertilization experiment that found that N significantly increased C‐degrading enzyme activities in low pH soils with wide C:N plant inputs but increases were less pronounced in limed soils with narrow C:N plant inputs (Cenini et al. ). Together, these findings suggest that microbes in the high C:N soils, represented here by ECM plots, can respond directly to increased N availability by producing more C‐degrading enzymes relative to N‐degrading enzymes.…”
Section: Discussionsupporting
confidence: 90%
“…Our results are also similar to those from a 19‐yr grassland fertilization experiment that found that N significantly increased C‐degrading enzyme activities in low pH soils with wide C:N plant inputs but increases were less pronounced in limed soils with narrow C:N plant inputs (Cenini et al. ). Together, these findings suggest that microbes in the high C:N soils, represented here by ECM plots, can respond directly to increased N availability by producing more C‐degrading enzymes relative to N‐degrading enzymes.…”
Section: Discussionsupporting
confidence: 90%
“…For example, Cenini et al. () show how an increase in microbial energy demand (i.e., C demand) as a result of low C:N plant detritus inputs in the same fertilized grasslands will increase the activity of the C‐acquiring enzyme β‐1,4‐glucosidase. The increased activity of this enzyme was then linked to more C being processed and accumulated (including microbial biomass C) into organo‐mineral soil pools.…”
Section: Discussionmentioning
confidence: 99%
“…, Cenini et al. ). Key knowledge gaps remain about how long‐term grassland management might influence plant tissue chemistry, and whether or not changes in plant element stoichiometry (e.g., C:N:P ratios) might be related to predictable changes in soil C, N, and P content (%) and storage (i.e., soil C, N, and P pools).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study shows, for example, how the addition of plant biomass to soils from different cover crops is positively related to both BG activity and soil C sequestration (Peregrina et al, 2014). Once BG has been produced and released into the soil, it could potentially be disabled through binding to mineral and organic colloids (Allison and Jastrow, 2006) thus contributing (together with other microbial 'waste' products) to the accumulation of C in soils (Cotrufo et al, 2013;Cenini et al, 2015).…”
Section: Tablementioning
confidence: 99%